Accounting Beta as Ex Ante Uncertainty Proxy in Initial Public Offering - Tatang Ary Gumanti; Dwi Venita Wiandani (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to examine the relation between accounting measures of total firm risk and the level f underpricing of initial public offerings (IPOs). A number of studies have shown an association between market and accounting betas. However, most of the studies are performed using a sample of large established firms for which both accounting and market betas can be computed. In case of IPO firms, market betas cannot be computed due to the data limitations associated with private firms. Due to limited information available prior to IPO dates, in particular financial reports, one has to use a proxy to measure risk in an IPO. Accounting variables have been prominently known as potential proxy for ex ante uncertainty in an IPO.Using a sample of 90 IPOs that went public during 1991-1997 at the Jakarta Stock Exchange, this study finds that the level of underpricing is determined by accounting beta, price to book value ratio and price earnings ratio. The IPO issue size has negative but insignificant association with the level of underpricing.